2012
DOI: 10.1021/jm2017336
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Preliminary Biological Evaluation of 6-O-Glucose–Azomycin Adducts for Diagnosis and Therapy of Hypoxic Tumors

Abstract: Several 2-nitroimidazole-based molecules (NIs) are used as clinical hypoxic tumor radiodiagnostics, but they are not effective as radiosensitizers/radiochemotherapeutics. These NIs permeate tumor cells nonselectively via diffusion, and in therapy, where high doses are required, their dose limiting toxicities preclude success. The synthesis and preliminary in vitro evaluations of three glucoazomycins, members of a novel class of C6-O-glucose-linked-azomycin conjugates that are putative substrates of glucose tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Several glucose-linked drugs designed to deliver attached therapeutics to tumours that overexpress a glucose transporter are also undergoing clinical evaluation or late preclinical development [171][172][173] . Most notably, glufosfamide -a glucose conjugate of iphosphoramide -has advanced to Phase III clinical trials (NCT01954992) 174 , in which it is being assessed for treatment of metastatic pancreatic cancer.…”
Section: Mip-1072mentioning
confidence: 99%
“…Several glucose-linked drugs designed to deliver attached therapeutics to tumours that overexpress a glucose transporter are also undergoing clinical evaluation or late preclinical development [171][172][173] . Most notably, glufosfamide -a glucose conjugate of iphosphoramide -has advanced to Phase III clinical trials (NCT01954992) 174 , in which it is being assessed for treatment of metastatic pancreatic cancer.…”
Section: Mip-1072mentioning
confidence: 99%
“…The synthesis and preliminary biological evaluation of a series of glucose-azomycin adducts were recently reported in 2012 by Kumar and coworkers [63]. 2-nitroimidazole compounds have been studied in clinical trials as radiosensitizers.…”
Section: Current Progress In Glucose Conjugation As An Anticancer mentioning
confidence: 99%
“…To assess whether the uptake of these glucose conjugates was partially GLUT receptor-mediated, glycoconjugates were tested at concentrations ranging from 100 μM to 10 mM for the ability to compete with 14 C glucose uptake in Xenopus oocytes, which express GLUT-1. The compound depicted in Figure 8b, a diastereomeric mixture of α and β glucose conjugated at the 6 position to 3-carbon linker, off of which emerges a fluorine diagnostic arm and azomycin, was shown to be the strongest competitor for glucose uptake [63], suggesting that its cellular transport is at least partially GLUT-1 mediated. In vivo studies using glucoconjugated azomycins were not reported.…”
Section: Current Progress In Glucose Conjugation As An Anticancer mentioning
confidence: 99%
“…This compound also proved to be an effective radiosensitizer in multiple cancer cell lines using radiation doses up to 18 Gy. 96 …”
Section: Sugar-conjugate Compounds Interacting With Glutsmentioning
confidence: 99%